Crossing the border from preservice to inservice science teacher : research-based induction as professional development - Sunal, Dennis W.; Sunal, Cynthia S.; Ogodo, Justina A. (Research in science education., 2024)
"This RISE volume examines various approaches researchers have used to induct new teachers and mitigate the high turnover rates. Crossing the Border from Preservice to Inservice Science Teacher: Research-based Induction as Professional Development offers readers various tested strategies for supporting and retaining early-career science teachers. Some of the common tested effective strategies involve increasing teacher reflection, fostering teacher leadership, developing collegial collaboration, strengthen teacher identity, introducing PLC involvement in both preservice and inservice settings, expanding IHE teacher preparation to more deeply include classroom teachers, using graduate coursework to introduce induction PD and long-term follow-up of early career teachers. The contributing authors explain different approaches successfully implemented in various settings and their impact on developing high-quality teachers with the self-efficacy to positively impact student learning. The ideas provided in the volume can be replicated in-part and whole in other settings with the potential for similar results"-- Provided by publisher.